Dr. Simeon Ehui, IITA Director General's video on his one year in office - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
In this interview, IITA Director General Dr. Simeon Ehui talks about his one year in office, and how the institute has strengthened partnerships towards transforming agriculture in Africa. Some of the staff also had a few things to say about his leadership impact.